PT UNILEVER INDONESIA'S REPUTATION AND PROFITABILITY RECOVERY STRATEGY IN OVERCOMING BOYCOTT ACTION - Ade Mahendra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The rapid growth of digital communication has transformed corporate reputation into a dynamic construct shaped by interactions among multiple stakeholders, making multinational companies increasingly vulnerable to boycott movements and cancel culture. This study aims to analyze the reputation crisis experienced by PT Unilever Indonesia following the boycott movement using the Corporate Rhetorical Arena Theory (CRAT) and to formulate an effective reputation recovery strategy based on Image Restoration Theory (IRT). A qualitative case study approach was employed through in-depth interviews, non-participant observation of digital communication, and document analysis involving corporate reports, press releases, news coverage, and social media content. Data were analyzed using thematic analysis supported by triangulation to ensure credibility. The findings reveal that the reputation crisis was not primarily driven by the company's official communication but by multi-actor interactions involving consumers, digital communities, influencers, media organizations, and civil society groups. Although the company implemented communication strategies emphasizing reducing offensiveness and corrective action, these efforts were insufficient to counter rapidly evolving digital narratives. This study proposes an integrative reputation recovery model consisting of Transparency Hub, Digital War Room, Active Dialogue, and Local Value Proof. The model represents the study's theoretical contribution by integrating CRAT and IRT into a comprehensive framework linking multi-actor crisis communication, reputation recovery, stakeholder trust, and sustainable corporate profitability.